Comparison study of different value at risk models and their effectiveness on the Malaysian palm oil futures (FCPO) market - Thirunavukkarasu, L K. Suppiah (2015)
Market risk is an important element of derivatives trading and can cause derivatives market participants to suffer substantial amount of loss if not managed properly. Value at Risk (VaR) is a tool that has been used to manage market risk particularly in the developed markets. This research tries to identify which VaR model out of three models namely Historical Simulation, Delta Normal and Age Weighted Historical Simulation that can be effectively used as risk management tool for Malaysian derivatives market particularly the Malaysian Palm Oil Futures (FCPO) market. The back testing process was conducted to study the number of violations of each models produced and the exceptions were tested using Kupiec Proportion of Failure (POF) test to find the most accurate model. The study revealed that the Age Weighted Model was the most effective and robust compared to the other two models. Age Weighted potentially can be a viable alternative method of market assessment along with more complex models such as Monte Carlo Simulation and GARCH